ANALISIS PELAKSANAAN MANAJEMEN FASILITAS DAN KESELAMATAN BERBASIS SNARS EDISI 1 TAHUN 2018 DI RSU DELI MEDAN TAHUN 2020 - Meilani Lie (Jurnal Inovasi Kesehatan Masyarakat, 2020)
Facilities Management and Safety Standards (FMS) is one of the 15 hospital accreditation standards that must be fulfilled. FMS standards are very closely related to the implementation of Hospital Occupational Safety and Health (OSH). If the OSH is not implemented, the FMS standard cannot be fulfilled which impacts the quality of health services. This research aims to analyze the implementation of Facilities and Safety Management based on the Hospital Accreditation National Standards (HANS) 1st Edition 2018 at Deli Hospital Medan. The type of research is a qualitative study using a phenomenological approach. The research period is from December 2019 to March 2020. The number of informants are 10 people (1 person in charge of accreditation and 9 people in charge of OSH). Data collection is done through in-depth interviews, document checks and observations. Data were analyzed with descriptive statistics to describe the achievements of each FMS standard and continued with thematic analysis to conclude the results of the interview. The results showed that the achievements of FMS based on HANS 1st Edition obtained an average of 61.90%. Obstacles to fulfillment include: limited availability of facilities and infrastructure, limited number of Human Resources (HR), awareness of HR, lack of HR knowledge about OSH, limited budget allocation to support the implementation of FMS standards, readiness of the training in conducting training and simulation has not been maximized, the lack of compliance of the Hazardous and Toxic Waste provider to attach the Material Safety Data Sheets. Achievement of FMS standard fulfillment based on HANS Edition 1.1 was 67.14%, but did not become an obstacle in hospital accreditation from the First rank to the Basic rank. It is expected that the person in charge of accreditation prioritizes the improvement of FMS 2 (implementing facilities and environmental risk management programs), FMS 6 (developing, maintaining, disaster management programs to respond to disasters and natural disasters) and FMS 6.1 (conducting simulation handling / responding to emergencies, epidemics and disasters ) because the fulfillment is still <50%. Hospital management should do a simulation before accreditation from Hospital Accreditation Commission to fulfill the achievement of at least 80%, add competent human resources in the field of OSH which also plays a role in assisting the implementation of FMS standards and allocating funds for training activities. Keywords: Hospital, Accreditation, Facilities Management and Safety